2017
DOI: 10.13031/aea.11963
|View full text |Cite
|
Sign up to set email alerts
|

Field Characterization of Field Capacity and Root Zone Available Water Capacity for Variable Rate Irrigation

Abstract: Abstract. Accurate spatial characterization of field capacity (FC) and root zone available water capacity (R) can enhance site-specific management practices—such as variable rate irrigation—to lower input costs, reduce contaminant leaching, and/or improve crop yield. Measuring the volumetric water content after wet soils drain following substantial precipitation can provide a field estimate of FC. The average FC (FCa) for the managed root zone was determined at thirty-two locations in a topographically variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 29 publications
(48 reference statements)
3
19
0
Order By: Relevance
“…Martin et al (1990) demonstrated that "good indication of the field capacity water content can be determined by sampling field soils one to three days after a thorough irrigation or rain and when crop water use is small." This suggestion is consistent with the concept of FC obs (Lo et al, 2017). In this study, the FC obs was determined for the Yutan and Fillmore soil types from the graph of temporal trends in root zone water depth from the in situ GS-1 data (fig.…”
Section: Implications For Irrigation Managementsupporting
confidence: 86%
See 1 more Smart Citation
“…Martin et al (1990) demonstrated that "good indication of the field capacity water content can be determined by sampling field soils one to three days after a thorough irrigation or rain and when crop water use is small." This suggestion is consistent with the concept of FC obs (Lo et al, 2017). In this study, the FC obs was determined for the Yutan and Fillmore soil types from the graph of temporal trends in root zone water depth from the in situ GS-1 data (fig.…”
Section: Implications For Irrigation Managementsupporting
confidence: 86%
“…For field irrigation applications,  MAD is generally considered to be 50% of the plant-available water of the soil type, as error in  v measurement may result in unintended crop stress. The FC ( FC ) for the experimental site (silty clay loam soil) was 40% on average, and 50% MAD was attained at  MAD of 28% based on past studies (Barker et al, 2017;Lo et al, 2017). Therefore, as a part of the laboratory experiment, the soil was saturated initially and then readings were taken from  v of 41.5% to 28%, recording the weight at increments of 1.5%  v .…”
Section: Experiments Descriptionmentioning
confidence: 99%
“…The water balance models required both field capacity (FC) and permanent wilting point (WP) for each plot. Plot FC was determined based on neutron probe readings (Lo et al, 2017, who cite Martin et al, 1990. Volumetric soil water content readings from June 30 and July 1, 2015, were used for this purpose for the 2015 season at Mead.…”
Section: Water Balance Models For Irrigation Schedulingmentioning
confidence: 99%
“…1, 2). The gSSURGO data were also used to develop R maps for the two study fields since R could be spatially estimated without the need for field data collection (Lo et al 2017). The gSSURGO data include AWC values for soil horizons, along with their depth.…”
Section: Development Of Root Zone Available Water Capacity Mapsmentioning
confidence: 99%
“…One necessity for writing a prescription map is defining IMZs. Of the different methods for delineating IMZs, a common one is based on observed changes in soil properties (Lo et al 2017). The range in R determines the number, size and distribution of IMZs (Daccache et al 2015).…”
Section: Introductionmentioning
confidence: 99%